Examination of the effects of archery exercises on some physical parameters of university students - TURKMEN, Mutlu; KUL, Murat; GÖNEN, Mevlüt; KARATAŞ, İsmail and CEYHAN, Mehmet Ali and YILDIRIM, Ümit and TÜRKER, Üstün and USTABULUT, Mete Yusuf (Progress in Nutrition, 2022)
The aim of this study was to examine the effects of eight-week modern archery training on some physical parameters of university students. In the study, one-group pretest-posttest design from the experimental research methods was used. The study group consisted of a total of 25 voluntary- students chosen randomly 10 female and 15 male, undergraduate, and graduate levels during the fall semester of the 2020-2021 academic year at Bayburt University, who have not received Olympic archery training before. The Wilcoxon Signed Ranks Test was applied to analyse the data of the study. Regarding female participants, within the scope of Wilcoxon Signed Ranks Test results; according to the analysis results of the variables "Index Finger", "Middle Finger", "Ring Finger", statistically significant differences were found between the pretest and posttest values for each variable. Regarding male participants, within the scope of Wilcoxon Signed Ranks Test results; according to the analysis of the results of the participants’ "Back-Leg", "Index Finger", "Middle Finger" variables, statistically significant differences were found between the pretest and posttest values for each variable.